Hubungan disiplin kerja dengan kinerja pegawai di lingkungan dinas pendidikan pemuda dan olahraga kabupaten solok: Disiplin,kinerja - Selvia putri, Indri; Lusi Susanti (Global Action and Education for Society, 2023)
This research is based on the author’s observations at the Departement Of Education, Youth and Sports, Solok Regency regarding the relationship between work discipline and employee performance.employee the type of research used is correlational with the post facto es method. The population in this study is all employees who are the Departement of Youth and Sports Education, Solok Regency totalling 87 people and a sample of 46 people taken using stratified randoms sampling tecnhnique.the research instrument used is a questionnaire with Stalo Likert model consisting of 40 items that have been tested for validity and reliability. The data is processed using the product moment correlation formula is a Mean 89,9 Median 89,5 and mode 89 by comparing the mean score with the maximum score multiplied by 100% so that it can be seen that the employee performance is at a very good score with a score of 92% while the level of work discipline there is a Mean score of 86,48 Median 86,5 and Mode 82 by comparing the Mean score with a maximum score multiplied by 100% so that it can be seen that work discipline is at a very good score with a score of 91% . the haul product moment correlation analysis obtained ring 0,290078>Table 0,284 thus it can be concluded that there is a relationship between work discipline and employee performance.